Hyperparathyroidism caused by a functional parathyroid cyst. (21st June 2013) - Suzuki, Kunihiro; Sakuta, Ayuko; Aoki, Chie; Aso, Yosimasa
Abstract : A 67-year-old Japanese woman was admitted to our hospital for malaise and loss of appetite. Relevant biochemical examinations showed definite hypercalcaemia and elevated serum levels of intact parathyroid hormone (PTH). We performed thyroid ultrasonography and CT of the neck, which revealed a cystic lesion in the right lower lobe of the thyroid glands. Ultrasound-guided fine-needle aspiration was performed, and PTH level of the cystic fluid was markedly elevated. Technetium-99m-hexakis 2-methoxyisobutyi isonitrile sesta scintigraphy showed intense ring-shaped accumulation of radioactivity in the wall of the cyst. The patient underwent a right lobectomy to resect the cystic parathyroid adenoma. After surgery, her serum calcium and PTH level returned to normal ranges.